(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Arab thinkers disagreed about the nature of Orientalism, and its goal of studies and extensive research of the East since the thirteenth century AD, and differed views and differed from one thinker to another, that the goal of Orientalism is religious, cognitive, political, but the Hassan Hanafi did not shorten Orientalism in these reductions, but wanted Research in Orientalism and work to benefit from it in the service of a revolutionary renaissance, and work to establish a new science called alienation is not anti-Orientalism, but a reading in its aspects, and wanted to use all the possibilities to establish his "Renaissance project" and philosophy at the social and political level, linked to the state of uncertainty in Arab thought M The issue of authenticity and modernity, his project began with a civilized position, establishing a system of values ​​and intellectual and philosophical implications adopted by the project, dividing the Arab trends to the front of the Arab-Islamic heritage and the position of him and the Western expatriate heritage and the position and reality front in all its dimensions, and that it can’t live without the cultural heritage And civilizational, and can’t be isolated from what is happening around you from the changes that have affected reality at all levels.